Highly Efficient Synthesis of 1,4-Disubstituted 1,2,3-Triazole Derivatives under Ultrasonic Irradiation, Evaluation of Vasorelaxant Activities - Sakineh Ebrahimpourmoghaddam; Maryam Motevasel; Saghar Mowlazadeh Haghighi; Azar Purkhosrow; Hashem Sharghi; Ali Khalafi-Nezhad; Elahe Sattarinezhad (Shiraz University of Medical Sciences, 2024)
1,4-Disubstituted 1,2,3-Triazole derivatives are exciting pharmacophores with a wide range of biological activities, including anticancer, antituberculosis, antifungal, antibacterial, and anti-HIV. Due to their diverse uses, many efforts have been made to synthesize these valuable medicinal scaffolds. Unfortunately, most of them have difficult and time-consuming procedures, low yields of the products, or environmentally toxic residues, therefore, it is necessary to develop easy methods with high efficiency and without harmful by-products. In the first part of this study, differently decorated 1,4-disubstituted 1,2,3-triazole derivatives were synthesized through a one-pot, two-step procedure from epoxides, alkynes and sodium azide in the presence of Cu2O in water under ultrasonic irradiation with high efficiency and without any toxic residues. In the second part of this research, the vasorelaxant activity of these triazole derivatives was studied in isolated rat thoracic aorta. Based on the results, three compounds have potent vasorelaxant activity and can be considered in future evaluations for the development of new antihypertensive drugs.